An Investigation into the Translation of General Power of Attorney Texts - Dr. Yousif Ali Omer (Journal of College of Education, 2025)
This study investigates the translation of specialized texts, with a particular focus on the legal domain, from English into Kurdish. More specifically, the English version of the General Power of Attorney genre and its Kurdish counterpart among legal texts are examined from both macro- and micro-translation analysis to identify issues that legal translators encounter while translating this text type. The macro-analysis explores certain essential aspects that help in achieving a deep understanding of this text type, emphasizing structural organization, function, and the legal and historical background of the document. On the other hand, the micro-analysis addresses specific linguistic aspects in relation to both source and target languages, including grammatical structures, terminology, and conventions. The study brings attention to the fact that differences in legal systems pose translation problems. The findings highlight the complexity of translating legal documents and stress the importance of a deep understanding of legal texts, legal systems, and the cultural contexts of both languages to provide translations that are equivalent to their original texts in terms of effectiveness.